2017
DOI: 10.3390/min7070125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Conditioning on the Flotation of Pyrrhotite in the Presence of Chlorite

Abstract: Abstract:The influence of conditioning on the flotation of pyrrhotite in the presence of chlorite was investigated through flotation tests, sedimentation tests, and X-ray photoelectron spectroscopy (XPS) analysis. The flotation results show that chlorite slimes dramatically impair the flotation of pyrrhotite. Sedimentation and flotation tests reveal that conditioning can effectively remove chlorite slimes from pyrrhotite surfaces, resulting in an enhanced flotation recovery of pyrrhotite. When mixed minerals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 27 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…Herein, all the peaks observed in the orange curve were attributed to the barite sample in agreement with previous reports. , Similarly, the results for celestite (shown in green) are supported by previous literature reports. , With regard to sulfide scales, XRD confirmed that the sample used herein is pure PbS. All the peaks, shown in purple at 2 theta of 26, 30, 43.5, 51, 63, 69, and 71° are for PbS. Pyrite sample results are given elsewhere, whereas the four peaks at 30, 34.5, 44, and 53.5° (in red color) are for pyrrhotite. Finally, carbonate scales are studied using the CaCO 3 sample with the XRD peaks illustrated in black and are in agreement with the published literature. , All samples were pure minerals as confirmed by the XRD results.…”
Section: Resultssupporting
confidence: 91%
“…Herein, all the peaks observed in the orange curve were attributed to the barite sample in agreement with previous reports. , Similarly, the results for celestite (shown in green) are supported by previous literature reports. , With regard to sulfide scales, XRD confirmed that the sample used herein is pure PbS. All the peaks, shown in purple at 2 theta of 26, 30, 43.5, 51, 63, 69, and 71° are for PbS. Pyrite sample results are given elsewhere, whereas the four peaks at 30, 34.5, 44, and 53.5° (in red color) are for pyrrhotite. Finally, carbonate scales are studied using the CaCO 3 sample with the XRD peaks illustrated in black and are in agreement with the published literature. , All samples were pure minerals as confirmed by the XRD results.…”
Section: Resultssupporting
confidence: 91%
“…The single mineral flotation was carried out in an XFG-type mechanical agitation flotation machine with a 40 mL cell [21]. The pyrite suspension was prepared by adding 2.0 g of pyrites, which was treated by 5 min ultrasonic pretreatment to 35 mL solutions.…”
Section: Flotationmentioning
confidence: 99%
“…In addition, the entrainment of minerals may be correlated with particle size [8]. However, most studies focus on the interaction between silicate and sulfide minerals rather than the entrainment, which also has a great influence on the concentrate grade of sulfide [9][10][11][12]. Thus, it is also very important to investigate the entrainment of chlorite in order to devise effective strategies for its elimination.…”
Section: Introductionmentioning
confidence: 99%